Injection moulding of 316L stainless steels reinforced with nanosize alumina particles - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2011)
This study aims to compare the effect of Al2O3 nanoparticle additions on the densification and mechanical properties of the injection moulded 316L stainless steels. The 316L stainless steel and Al2O3 nanoparticles were dry mixed and moulded using a wax based binder. The critical powder loading for injection moulding were 60 vol.-% for all samples. Debinding process was performed in solvent using thermal method. After the debinding process, the samples were sintered at 1405 degrees C for 60 and 120 min under vacuum. Metallographic examination was conducted to determine the extend of densification and the corresponding microstructural changes. The sintered samples were characterised by measuring tensile strength, hardness and wear behaviour. Wear loss was determined for all the samples after wear testing. All the powders, fracture surfaces of moulded and sintered samples were examined using scanning electron microscope. The sintered density of straight as well as Al2O3 nanoparticles reinforced injection moulded 316L stainless steels increases with the increase in sintering time. The additions of Al2O3 nanoparticles improve the hardness and wear resistance with the increase of sintering time.
Keywords: Powder injection moulding; 316L stainless steel powder; Sintering; Nanosized alumina